252 ASYMPTOMATIC HUMORAL REJECTION DIAGNOSED ON ENDOMYOCARDIAL BIOPSY AFTER HEART TRANSPLANT APPEARS TO HAVE CLINICAL SIGNIFICANCE. (1st January 2005) - Go, S. E.; Kobashigawa, J. A.; Patel, J. K.; Hamilton, M.
Abstract : Background: Humoral rejection (HR) has been associated with poor outcome after heart transplantation. The diagnosis of HR usually includes endomyocardial biopsy findings of endothelial cell swelling, intravascular macrophages, +C4d staining, and clinical findings of left ventricular dysfunction. However, the significance of findings of HR in the endomyocardial biopsies of heart transplant patients who are asymptomatic is unclear. Methods: We reviewed 246 patients between 7/97 and 9/01 for findings of HR in endomyocardial biopsies specimens. Patients were divided into 2 groups, Symptomatic Humoral Rejection (SHR) due to left ventricular dysfunction, and Asymptomatic Humoral Rejection (AsHR). A control group of 203 patients was used for comparison. Outcomes included 3-year survival and development of transplant coronary artery disease (TCAD). Results: Patients were considered to have HR if they had one or more endomyocardial biopsies specimen positive for HR. There were 22 patients in the SHR group, 21 patients in the AsHR group and 203 patients in the control group. There were more women in the HR groups than the control (SHR 41%, AsHR 43%, control 22%, p=0.021). The 36 months survival for the SHR, AsHR, and control groups was not significantly different (SHR 73%, AsHR 90%, control 79%, p=0.333). Freedom from the development of TCAD (≥30% stenosis) was significantly lower in both HR groups compared to control (SHR 59%, AsHR 50%, control 83%, p=0.001). There was no significant difference between AHR and AsHR for TCAD. Conclusion: Symptomatic HR and Asymptomatic HR compared to controls have similar survival at 36 months after heart transplant. Asymptomatic HR as well as Symptomatic HR patients have less freedom from TCAD compared to the control group. These patients should be considered for augmentation of immunosuppresion to possibly improve outcome (TCAD).